Analisis Penerapan Akuntansi Perpajakan pada Koperasi Simpan Pinjam Ikamala Larantuka - Aloysia Roma Rebu; Wilhelmina Mitan; Yoseph Darius Purnama Rangga (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the application of tax accounting at the Ikamala Larantuka Cooperative. This research uses a qualitative method with a qualitative descriptive and quantitative descriptive approach. The data collection techniques used are observation, interviews and documentation. The data analysis technique, namely qualitative data analysis, begins with the data reduction stage, data presentation and drawing conclusions and verification as well as analyzing financial report data with fiscal reconciliation in accordance with tax regulations and legislation. The research results show that the Ikamala Larantuka cooperative has implemented tax accounting, but several errors were still found in paying income tax (PPh) which was not in accordance with Minister of Finance Regulation No. 242/PMK.03/2014 concerning procedures for paying and remitting taxes and the financial reports presented by cooperatives are not in accordance with applicable tax laws and regulations due to differences in calculations in commercial financial reports and fiscal financial reports where there are differences in recognition of income and costs according to Income Tax Law Regulation Number 36 of 2008.